PSXIV-11 The use of essential oils alone or in combination with monensin for calf starters. (7th December 2018) - Casper, D; Guo, L; Ting, L; Wu, J
Abstract: Gut health is critically important and essential oils (EO) and monensin (MON) have been shown independently to improve calf gut health and growth rates. The objective was to evaluate EO and MON alone or in combination on calf growth performance. Eighty new born Holstein calves were randomly assigned to one of four treatments arranged in a 2 x 2 factorial (EO and MON) using a randomized complete block design with the initial measurements used as a covariate. Treatments were: 1) Control without EO or MON added to the calf starter (CS); 2) EO (40 g/ton) added to the CS (Stay Strong, Ralco Inc.); 3) MON (720 g/ton, 20%) added to the CS (Elanco, Inc.); and 4) EO and MON added to CS. Calves were fed colostrum followed by whole milk through weaning at 42 d and CS was fed ad libitum through the 70 d experimental periods. No significant ( P > 0.10) EO by MON interactions were detected. Calves fed a EO containing CS demonstrated greater ( P < 0.01) body weight (67.3 and 70.4 kg for without and with EO, respectively), while the main effect of MON was nonsignificant ( P = 0.69) calves fed MON (68.7 and 68.9 kg for without and with MON, respectively). Feeding a CS containing EO increased ( P < 0.01) ADG (0.84 and 0.95 kg/d) by 13% compared to calves fed without EO, while feeding calves a CS containing MON numerically (P = 0.46) increased ADG by 3.4% compared to calved fed a CS without MON (0.88 and 0.91 kg/d) through the 70 d. The increased ADG was an increase in frame growth. These data demonstrate that EO and MON in combination was not beneficial and that calf growth performance can be improved with EO.